Применение метода геометрической акустики для решения задач визуализации - Квасников К. Г. Константин Григорьевич; Солдатов А. И. Алексей Иванович; Болотина И. О. Ирина Олеговна; Крёнинг Х. М. В. А. Ханс Михаэль Вильхельм (Вильгельм) Адольф; Потапенко А. А. Алексей Алексеевич (2013, 2013)
Заглавие с экрана